MEMS‐based LC tank with extended tuning range for multiband applications. Issue 9 (22nd September 2016) - Cazzorla, A.; Farinelli, P.; Urbani, L.; Sorrentino, R.; Margesin, B.
Abstract: This paper presents the modeling, simulations, and measurements of a compact multiband microelectromechanical (MEMS)‐based LC tank resonator suitable for low phase noise voltage‐controlled oscillators (VCOs). The resonator is based on a high‐ Q spiral inductor and high capacitance ratio varicap fully integrated in FBK‐irst (Fondazione Bruno Kessler) MEMS manufacturing process. The design of the varicap is based on double‐actuation mechanism with a mechanical central bond that inhibits the pull‐in allowing for a theoretically infinite tuning ratio. The measurements have shown a total not continuous capacitance ratio ( Cr ) of 5.2 with a continuous variation of the capacitance values in the range 225 fF–600 fF which corresponds to a continuous capacitance ratio ( Cr *) of 2.6. The performance repeatability, the power‐handling capability, and the stability over time were tested on 10 samples showing a negligible variation of the capacitance values. The spiral inductor consists of a suspended gold membrane thick 5 µm in a circular shape which was modeled in order to optimize the quality factor ( Q ) in the frequency range 2–4 GHz. The measurement results show a Q of about 55 in the 2–4 GHz frequency band. The LC tank measurements show an overall tuning range better than of 45% in the 3.2–4.9 GHz frequency band, consisting of two continuous tuning ranges of 7.5% and 25%. The LC tank allowed the design of MEMS‐based voltage‐controlled oscillators (VCOs) with an overall tuning better than 60% in the frequency range 2.15 GHz–3.85 GHz and two separate regions of continuous tuning range. The VCO prototype will be fabricated on Surface Mount Technology on RO4350 laminate. The main figures of merit are presented in comparison with the state of the art. Key Points: The paper focuses on the implementation of the RF‐MEMS in tunable oscillators RF‐MEMS varicap and spiral inductor have been used for the design of the LC resonator By using ANSYS Multiphysics environment, the LC resonator was modeled and performance‐optimized range